2010
DOI: 10.1139/y10-037
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin on jejunal PepT1 expression and function regulation in diabetic male and female rats

Abstract: The aim of this study was to determine whether the jejunal oligopeptide transporter PepT1 is regulated by insulin and whether this regulation is sex-dependent in type 1 diabetic rats. PepT1 expression, real-time polymerase chain reaction, and Western blots were performed using jejunal segments from 4 groups of male and female rats: normal (nondiabetic), insulin-treated nondiabetic, streptozotocin (STZ)-induced diabetic (type 1 diabetes), and insulin-treated diabetic models. Furthermore, the same segments from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Interestingly, two mRNAs enriched in MetS-EVs were also enriched in MetS-MSCs, as we observed in a recent study [ 25 ]. The nuclear receptor subfamily-5 group-A member-1 (NR5A1, or steroidogenic factor-1), which modulates the expression of insulin-like factor 3, relaxin-like factor [ 48 ], and the oligopeptide transporter PepT1 solute carrier family-15 member-1 (SLC15A1), which is highly regulated by insulin [ 49 ]. These observations suggest that MetS alters mRNA expression related to insulin signaling in adipose tissue-derived MSCs and their daughter EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two mRNAs enriched in MetS-EVs were also enriched in MetS-MSCs, as we observed in a recent study [ 25 ]. The nuclear receptor subfamily-5 group-A member-1 (NR5A1, or steroidogenic factor-1), which modulates the expression of insulin-like factor 3, relaxin-like factor [ 48 ], and the oligopeptide transporter PepT1 solute carrier family-15 member-1 (SLC15A1), which is highly regulated by insulin [ 49 ]. These observations suggest that MetS alters mRNA expression related to insulin signaling in adipose tissue-derived MSCs and their daughter EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors including diet and infections probably modulate the abundance of specific taxa within the microbial ecosystem. Expression of the intestinal peptide transporter PEPT 1 is modified by oestrogen, so providing sex‐specific effects. The GPI ‐anchors are the major target of signalling via GPI ‐anchored proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, altered expression and function of intestinal PepT1 are also dependent on sex. For example, in Sprague-Dawley rats, it was reported that STZ-induced diabetes decreased the expression and function of intestinal PepT1 in male rats, but increased them in female rats [100]. Leptin and insulin deficiencies may contribute to the downregulation of intestinal PepT1 [101,102].…”
Section: Pept1mentioning
confidence: 99%